Development of MetaPolije : Cloud-Based Metabase GIS Data Analysis Platform - Purbaningtyas, Rani; Widianta, Moh Munih Dian; Albaab, Mochammad Rifki Ulil (International Journal of Technology, Food and Agriculture, 2024)
This study aims to discuss the successful development of MetaPolije. MetaPolije is a platform used for cloud-based spatial-text data analysis utilizing the metabase library. MetaPolije as an alternative solution for users who need a medium for textual data analysis while also displaying precise location data. This platform is developed following the stages of agile method, which consists of several stages, from system requirement to testing. The platform has also undergone functional, validity, and performance testing techniques to ensure its efficiency. The test results have shown that the platform is capable of functioning well according to its intended purpose. Additionally, the platform is able to accurately display visualized data analysis results, including precise location points for each datum. Therefore, it can be concluded that the MetaPolije is a viable platform that meets the standards of functional, validity, and performance testing, making it a dependable and effective tool for data analysis. MetaPolije has been successfully developed by providing the basic features needed by users when conducting spatial text data analysis. The test results indicate that MetaPolije has met the quality testing standards for software based on each specified testing indicator, covering functional, validity, and performance aspects. These features can also be customized according to the users' needs and purposes.